Branch-duct intraductal papillary mucinous neoplasms of the pancreas: to operate or not to operate?. Issue 8 (24th November 2006) - Salvia, Roberto; Crippa, Stefano; Falconi, Massimo; Bassi, Claudio; Guarise, Alessandro; Scarpa, Aldo; Pederzoli, Paolo
Abstract : Background: Branch-duct intraductal papillary mucinous neoplasms (BD-IPMNs) of the pancreas are reported to be less aggressive than the main-duct type. Hence, less aggressive treatment has been proposed for the former. Aim: To evaluate the effectiveness of a follow-up protocol for BD-IPMNs. Design: Prospective study. Setting: An academic tertiary referral centre. Patients: From 2000 to 2003, 109 patients with BD-IPMNs underwent trans-abdominal ultrasound and magnetic resonance cholangiopancreatography with secretin. Patients who presented malignancy-related parameters (size >3.5 cm, nodules, thick walls, carbohydrate antigen 19.9 level >25 U/l, recent-onset or worsened diabetes) and/or complained of symptoms were submitted to surgery (arm A). All asymptomatic patients without suspicion of malignancy were followed up according to a 6-month clinical–radiological protocol (arm B). Main outcome measures: The effectiveness of conservative management of BD-IPMNs. Results: 20 (18.3%) patients underwent surgery (arm A); pathological diagnosis of BD-IPMNs was always confirmed. 89 (81.7%) patients were followed up for a median of 32 months (arm B); of these, 57 (64%) patients had multifocal disease. After a mean follow-up of 18.2 months, 5 (5.6%) patients showed an increase in lesion size and underwent surgery. The pathological diagnosis was branch-duct adenoma in three patients and borderline adenoma in two. Conclusions: Surgery is indicated in <20% of cases of BD-IPMNs, and, in the absence of malignancy-related parameters, careful non-operative management seems to be safe and effective in asymptomatic patients. Although observation for a longer time is needed to confirm these results, our findings support the guidelines recently recommended by the International Association of Pancreatology.